2012
DOI: 10.1007/s00417-012-2078-5
|View full text |Cite
|
Sign up to set email alerts
|

The effect of hinge location on corneal sensation and dry eye after LASIK: a systematic review and meta-analysis

Abstract: According to the available data, we suggest that hinge location may have some effect on corneal sensation and dry eye syndrome after LASIK at the early postoperative period. However, there was no significant difference between the groups at 6 months after surgery. Further well-organized, prospective, randomized studies involving more patients are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 29 publications
0
26
0
Order By: Relevance
“…SMILE is a flapless surgery with a small incision that is made at the superior aspect of the eye. Since superior-hinged flap may cause severe loss of sensation and presence of dry eye syndrome than horizontal-hinged flap in LASIK, the temporal-hinged corneal flap was made in WFG FS-LASIK in the requirement of the Ethics Committee of Tianjin Eye Hospital [14, 15]. Thus, the corneal wound-healing response at the site of the superior incision could induce an asymmetry of aberration in the vertical direction [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SMILE is a flapless surgery with a small incision that is made at the superior aspect of the eye. Since superior-hinged flap may cause severe loss of sensation and presence of dry eye syndrome than horizontal-hinged flap in LASIK, the temporal-hinged corneal flap was made in WFG FS-LASIK in the requirement of the Ethics Committee of Tianjin Eye Hospital [14, 15]. Thus, the corneal wound-healing response at the site of the superior incision could induce an asymmetry of aberration in the vertical direction [27].…”
Section: Discussionmentioning
confidence: 99%
“…The temporal-hinged corneal flap was made in the requirement of the Ethics Committee of Tianjin Eye Hospital because studies showed horizontal-hinged flap may cause less loss of sensation and presence of dry eye syndrome than superior-hinged flap in LASIK [14, 15]. Refraction and wavefront information for the treated eyes was collected using a WaveScan system and after being carefully scanned and selected was transferred to the STAR S4 excimer laser system.…”
Section: Methodsmentioning
confidence: 99%
“…; Perez‐Gomez & Efron ; Feng et al. ; Wei & Wang ). Results in this study demonstrated less reduction in sub‐basal nerve density and the total number of nerves and nerve branches, in favour of SMILE.…”
Section: Discussionmentioning
confidence: 99%
“…By 6 months, no difference was seen between the groups. 51 Other intraoperative variables that have been linked to post-LASIK dry eye include hinge flap width, flap thickness, and ablation depth. The hypothesis is that wider hinge flaps, thinner flaps, and lower ablation depths preserve more corneal nerves, thereby reducing the risk of dry eye disease.…”
Section: ' Intraoperative Risk Factorsmentioning
confidence: 99%